Hubungan Tingkat Pengetahuan Terhadap Kepatuhan Minum Obat Antihipertensi Pada Pasien Hipertensi di Rumah Sakit X Kabupaten Malang Tahun 2025 - Ahmad Wildan Waviulahdi; Endang Setyowati; Fahrudin Arif (Universitas Respati Indonesia, 2026)
Hypertension is a chronic disease with an increasing prevalence and is often undetected in the early stage due to the lack of specific symptoms. Poor blood pressure control may lead to complications affecting vital organs. This study aimed to analyze the relationship between patients’ knowledge about hypertension and their adherence to antihypertensive medication. This research employed a quantitative approach with a cross-sectional design. A total of 80 hypertensive outpatients were selected using a purposive sampling technique at Hospital X in Malang Regency from July to November 2025. Data were collected using validated and reliable questionnaires. Data analysis was performed using univariate and bivariate analysis with the Chi-Square statistical test at a significance level of 0.05. The results showed that most respondents had a good level of knowledge (53 respondents; 66.3%), while 27 respondents (33.7%) had lower knowledge levels. Most respondents demonstrated high medication adherence. However, statistical analysis indicated no significant relationship between knowledge level and medication adherence among hypertensive patients (p>0.05). Therefore, knowledge level was not significantly associated with antihypertensive medication adherence in this study.